Meaning of life as perceived by nurses at work in oncology palliative care: a phenomenological study - Renata Carla Nencetti Pereira Rocha; Eliane Ramos Pereira; Rose Mary Costa Rosa Andrade Silva; Angelica Yolanda Bueno Bejarano Vale de Medeiros; Diva Cristina Morett Romano Leão; Aline Miranda da Fonseca Marins (SciELO, 2021)
ABSTRACT Objective: To understand the meaning of life as perceived by nurses at work in oncology palliative care. Method: This is a qualitative study, with a phenomenological approach, based on the theoretical-philosophical framework by Viktor Emil Frankl. It was developed with nurses in a unit specialized in oncology palliative care located in the city of Rio de Janeiro and used phenomenological interviews. Data were processed using the phenomenological method by Amedeo Giorgi. Results: Thirty-four nurses participated in the study. The study conveys an existential message to nurses through selftranscendence. Through their work, they represent their own identity, which is directly impacted by the way they perceive freedom and responsibility in the face of actions taken. They build their reality and make work viable as a source of life. The care provided is no longer just a task to be qualified as a solidary, relational, existential, dynamic, and temporal issue. Conclusion: The experience in a scenario of life finitude allows these professionals to experience an authentic encounter with their self, the awakening of values giving meaning to their existence, and self-transcendence, deeply contributing to society through a more human, comprehensive, and quality assistance.